Establishment of a novel experimental system for studying the photoperiodic response of short-day dicots using soybean ‘cotyledon-only plant’ as material - Zhang, Chunlei; Xu, Xin; Chen, Fulu; Yuan, Shan; Wu, Tingting; Jiang, Bingjun; Sapey, Enoch; Wu, Cunxiang; Sun, Shi; Guo, Changhong; Han, Tianfu (Frontiers in Plant Science, 2023)
Soybean is an important model crop for photoperiodic response studies in plants and contributes significantly to the study of plant development and physiology in the past century. However, due that it is much bigger in size and longer in life cycle than Arabidopsis, it needs much more space for growth and time for investigation, which significantly hamper the efficiency of research. In the current study, we tested the photoperiodic response of a distinctive artificially-made cotyledon-only plant (COP) using a photoperiod-sensitive soybean variety Zigongdongdou (ZGDD) and other varieties with diverse sensitivity to photoperiod. ZGDD COPs flowered 39.4 ± 2.5 d after emergence under short-day conditions but maintained vegetative growth under long-day and night break conditions, which is similar to the case in the intact ZGDD plants. The COPs of early-maturing and medium-maturing soybean varieties also grew and flowered normally under natural day-length conditions. At the molecular level, the key genes in the photoperiodic pathway such as E1, GmFT1a, GmFT2a, and GmFT5a in the COPs also showed the same photoperiod sensitivity as in the intact plants. In addition, a simpler material of COP with only one cotyledon and root was generated and found to be sensitive to photoperiod as well. Notably, the COPs are only one-fifth the height of intact plants and one-third the maximum diameter of the intact plants grown in chambers 30 d after emergence. Based on COPs, we established a novel experimental system characterized by an entire photoperiodic response and longer longevity of cotyledons in addition to small plant size, ensuring the consistency, reliability, and stability of plant materials. COPs have the potential to be a novel model material for studies of the developmental biology of soybean and other dicots.